Efectuati urmatorul calcul: 9x⁴y⁴z⁴ : ( xyz² )² + (₋12x²y³z⁴ ) : (₋3yz⁴)+(3x²y²z ₋ 6x²y²z) : (3z)
Răspunsuri la întrebare
Răspuns de
3
9X^4Y^4Z^4:X^2*Y^2*Z^4=9X^2*Y^2
-12X^2Y^3Z^4: -3YZ^4=4X^2*Y^2
(3x²y²z ₋ 6x²y²z) : (3z) = (-3X^2*Y^2*Z) : 3Z= - X^2Y^2
adunam rezultatele
9X^2*Y^2 +4X^2*Y^2 - X^2Y^2=12 *X^2Y^2
-12X^2Y^3Z^4: -3YZ^4=4X^2*Y^2
(3x²y²z ₋ 6x²y²z) : (3z) = (-3X^2*Y^2*Z) : 3Z= - X^2Y^2
adunam rezultatele
9X^2*Y^2 +4X^2*Y^2 - X^2Y^2=12 *X^2Y^2
Alte întrebări interesante
Matematică,
9 ani în urmă
Chimie,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă